Adolescent Experiences from Participating in Extracurricular and Community-based Activities - Rosemary V. Barnett (EDIS, 2005)
There is little debate remaining in the field of youth development that participation in extracurricular and community-based youth activities (sports, school and community organizations, arts groups, etc.) provides a rich context for positive youth development. Research has found that structured youth activities encourage positive youth development. Now we need to examine critically why and how as well as what types of developmental changes occur within the context of youth activities (Benson & Saito; 2000; Roth et al., 1998; Dworkin, Larson & Hansen, 2003). This document is FCS2239, one of a series of the Family, Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: December 2005.